ESTIMATION OF HEAVY METAL TOLERANCE AND ANTIBIOTIC SUSCEPTIBILITY OF Bacillus cereus ISOLATED FROM MUNICIPAL SOLID WASTE - MAHAMUDA KHATUN; PARAMITA BERA; DEBMALYA MITRA; ANURUP MANDAL; AMALESH SAMANTA (International Journal of Pharma and Bio Sciences, 2012)
With the intension to screen heavy metal tolerance and antibiotic susceptibility, a bacterium was isolated and characterized from municipal solid waste dumping yard (Dhapa), Kolkata, India. On the basis of biochemical and 16S rDNA sequence profile, it was identified as Bacillus cereus. Tolerance was observed against heavy metals like Cd2+, Co2+, Ni2+, Cr3+, Pb2+ , Hg2+ by this bacterium and was found that the bacterium was most tolerable to Cd2+ and Cr3+ compared to other four metals. Study of susceptibility of this bacterium was determined by minimum inhibitory concentration (MIC) value of different antibiotics such as chloramphanicol, carbenicillin, tetracycline, erythromycin, ciprofloxacin, norfloxacin and maximum inhibition was observed by chloramphanicol and norfloxacin. A plasmid was isolated from the selected stain with MW of 45 kb. The plasmid curing experiment revealed that this plasmid was very essential for metal resistance power of the selected isolate.